Impacts of spruce budworm defoliation on the habitat of woodland caribou, moose, and their main predators. Issue 3 (18th March 2022) - Chagnon, Catherine; Bouchard, Mathieu; Pothier, David
Abstract: Forest logging has contributed to the decline of several woodland caribou populations by causing the fragmentation of mature coniferous stands. Such habitat alterations could be worsened by spruce budworm (SBW) outbreaks. Using 6201 vegetation plots from provincial inventories conducted after the last SBW outbreak (1968–1992) in boreal forests of Québec (Canada), we investigated the influence of SBW‐caused tree defoliation and mortality on understory vegetation layers relevant to woodland caribou and its main predators. We found a positive association between severe outbreaks and the cover of most groups of understory plant species, especially in stands that were dominated by balsam fir before the outbreak, where a high canopy openness particularly benefited relatively fast‐growing deciduous plants. Such increases in early successional vegetation could provide high‐quality forage for moose, which is likely to promote higher wolf densities and increase predation pressure on caribou. SBW outbreaks may thus negatively affect woodland caribou by increasing predation risk, the main factor limiting caribou populations in managed forests. For the near future, we recommend updating the criteria used to define critical caribou habitat to consider the potential impacts of spruce budworm defoliation. Abstract : Spruce budworm outbreaks affect boreal forest structure and cause an increase in the cover of understory plant species. This could have negative impacts on woodland caribou populations in eastern Canada by increasing the abundance of alternate preys for key caribou predators.